Adsorption Behavior of Acid-Leached Clays in Bleaching of Oil: A Descriptive Study - Mukasa-Tebandeke, I. Z.; Ssebuwufu, P. J. M.; Nyanzi, S. A.; Nyakairu, G. W.; Ntale, M.; Lugolobi, F.; Andreas, Schumann (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
This study has aimed at using the nature of adsorptive processes that occur during bleaching of vegetable oils using clays to characterize the bleaching of oils. The available data have shown that acid-leached clays had sites for adsorption of impurities in oils. Data obtained on residual impurities in cotton and sunflower-seed oils bleached with the same clay materials produced linear Langmuir and Freundlich isotherms. The increase in constant, k with increase in both temperature of thermal activation and concentration of acid used to leach the clay, suggests that bleaching efficiency increased. The value of n decreased with increase in temperature of activation and concentration of acid used to leach the clay suggesting that bleaching capacity increased. The mineral compositions of the clays influenced their surface, structural and bleaching properties.